Yo no soy una conversa: Gabriela Mistral y su tensión a los paradigmas espirituales. - LIRA OLIVARES, CAMILA (Nomadías)
This article examines the configuration of Gabriela Mistral's heterodox religiosity through her critical engagement with the spiritual paradigms of early twentieth-century Chilean institutional Christianity. In dialogue with Edward Said's concept of worldliness and Raymond Williams's notion of structures of feeling, it argues that Mistralian spirituality is constructed as a dynamic system of beliefs, deeply situated in lived experience and shaped by errancy, a profound bond with nature, and an early and sustained reading of the biblical text, as well as by Eastern influences and local forms of knowledge. Through the analysis of poems, prose texts, prayers, and intimate records related to death and suicide-particularly in relation to Romelio Ureta and her adopted son Yin Yin--the article explores how Mistral subverts orthodox notions of guilt, salvation, and transcendence. It contends that her writing displaces religious ritual into the intimate and domestic sphere, articulating a spirituality grounded in compassion, mourning, and insistent prayer, which challenges the normative discourses of the Catholic tradition and proposes an embodied, non-dogmatic spiritual ethics.